Voting over law enforcement: Mission impossible - Hakan İnal (SERIEs - Journal of the Spanish Economic Association, 2015)
Median voter theorem has been used in many economic environments including law enforcement. Assumptions of the median voter theorem, however, are generally violated in lawenforcement models. Moreover, it is impossible to have agents with "opposite equilibrium preferences" over enforcement levels in law enforcement models. These limitations on the use of preferences over law enforcement raises questions about the robustness and validity of law enforcement models.
Keywords: D62; D7; K14; K42; 330; Public enforcement; Equilibrium preferences; Enforcement equilibrium; Median voter theorem; Single-peaked preferences; Single-crossing property